Implementing remote triage in large health systems: A qualitative evidence synthesis. Issue 1 (15th December 2020) - Lewinski, Allison A.; Rushton, Sharron; Van Voorhees, Elizabeth; Boggan, Joel C.; Whited, John D.; Shoup, John P.; Tabriz, Amir A.; Adam, Soheir; Fulton, Jessica; Gordon, Adelaide M.; Ear, Belinda; Williams , John W.; et al.
Abstract: Remote triage (RT) allows interprofessional teams (e.g., nurses and physicians) to assess patients and make clinical decisions remotely. RT use has developed widespread interest due to the COVID‐19 pandemic, and has future potential to address the needs of a rapidly aging population, improve access to care, facilitate interprofessional team care, and ensure appropriate use of resources. However, despite rapid and increasing interest in implementation of RT, there is little research concerning practices for successful implementation. We conducted a systematic review and qualitative evidence synthesis of practices that impact the implementation of RT for adults seeking clinical care advice. We searched MEDLINE®, EMBASE, and CINAHL from inception through July 2018. We included 32 studies in this review. Our review identified four themes impacting the implementation of RT: characteristics of staff who use RT, influence of RT on staff, considerations in selecting RT tools, and environmental and contextual factors impacting RT. The findings of our systemic review underscore the need for a careful consideration of (a) organizational and stakeholder buy‐in before launch, (b) physical and psychological workplace environment, (c) staff training and ongoing support, and (d) optimal metrics to assess the effectiveness and efficiency of implementation. Our findings indicate that preimplementation planning, as well as evaluating RT by collecting data during and after implementation, is essential to ensuring successful implementation and continued adoption of RT in a health care system.